Sustainable geo tourism bridging geo heritage and culture through natural and landscape conservation / Wan Norazian Mohamad Ramli, Alamah Misni and Muhammad Adam Zakaria - Mohamad Ramli, Wan Norazian; Misni, Alamah; Zakaria, Muhammad Adam (College of Built Environment, 2023)
Gunung Lang development collaboration by Ipoh City Council and National Landscape Deparment in 1999 is only for eco-tourism, research and education.